STRATEGIES FOR PREVENTION OF POSTOPERATIVE DELIRIUM - ANESTHESIOLOGY ASPECTS - Jovanovic, Vesna; Petrovic, Natasa; Jovicic, Jelena; Lazic, Milos; Sipetic Grujicic, Sandra; Ladjevic, Nebojsa (Medical Research, 2025)
The occurrence of postoperative delirium is a significant health problem in critically ill elderly patients. The incidence of postoperative delirium varies in different studies and ranges from 10 to 70%. A higher incidence was noted among the elderly population, as well as after major surgical procedures such as vascular, cardiac, and hip fracture operations. This syndrome is associated with many adverse outcomes that can negatively affect patient hospitalization, prolong mechanical ventilation, increase mortality, and increase treatment costs. Affected patients are at increased risk of readmission and have a low quality of life. The best strategy for reducing the harmful consequences of postoperative delirium is its prevention. It has been shown that simple perioperative interventions can significantly reduce the incidence and severity of this syndrome. These are, above all, an assessment of cognitive function before surgery, avoidance of benzodiazepines, intraoperative monitoring of anesthetic depth, adequate control of postoperative pain, and maintenance of normotension and normothermia.
Keywords: postoperative delirium, postoperative cognitive dysfunction, risk factors, prevention